Evaluasi Status Gizi Atlet Pusat Pendidikan Latihan Pelajar (PPLP) Panahan Provinsi Riau - Alfindo, Muhammad Reski; Sasmarianto, Sasmarianto (ANTHOR: Education and Learning Journal, 2023)
The purpose of this research was to determine the Evaluation of the Nutritional Status of Archery Athletes of the Riau Province Student Training Center (PPLP). The type of this research is descriptive. The population and sample in this study were Archery Student Training Center (PPLP) Athletes of Riau Province, totaling 8 people. The research instrument used was to measure the body mass index owned by the Archery Student Training Center (PPLP) Athlete of Riau Province. The data analysis technique used is to calculate the percentage value of the nutritional status category of Archery Student Training CenterAthletes (PPLP) of Riau Province. Based on the description of the results of the research onthe Nutritional Status of Archery Student Training Center (PPLP) Athletes in Riau Province, it is known from the results that in the Underweight category (mild level of weight loss) there were 5 people (41.67%), in the Normal category there were 2 people (16.67%) , Obese category (light weight excess) as many as 1 person (8.33%). This shows that the Archery Students (PPLP) of Riau Province show that 2 athletes are in good condition. By having normal nutritional status, it means that the nutritional needs of the body are met, so that the body has sufficient energy to train and compete.